Industry 4.0: building and the new training demand - Adriana Scarlet Sferra (Agathón)
A comparison between Schools of Architecture requires a preliminary analysis of the political, economic and social contexts within which systems, education and projects are placed. An analysis is necessary to evaluate suitable educational experiments, such as the one presented here in the fields of Architectural Technology, particularly attentive to the quality of the project, to the essential understanding of the construction sector’s transition to Industry 4.0 and the new needs expressed by society. The first positive results outline possible paths that could be hoped for with a greater and more adequate availability of resources to Universities.